Business Analysis of Shrimp Trap Fishing Equipment (Trammel Net) In Nagari Sasak District Sasak Ranah Pasisie, West Pasaman District West Sumatera Province - Deriza Anggrioni Zandi; Hendrik Hendrik; Hazmi Arief (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted in March-April 2017 in Sasak Nagari District Sasak Ranah Pasisie West Pasaman District West Sumatera Province. This study aims to determine the gross revenues and net income of Fishing Jar. And to know the feasibility of Shrimp nets. The method used in this study is a survey method with the number of respondents as many as 30 people, where the determination of respondents conducted by census using the questionnaire that has been provided.The results of this study indicate a profitable fishing business based on Gross Income (GI) from fishing gear business Shrimp per year as much as  / 160 IDR. 64.613.000, - and net net income of Shrimp nets is IDR. 46.225.502, -per year. Based on financial analysis based on RCR calculation result of Shrimp fishing effort is 3.5 which means bigger 1 RCR> 1, then this business can be continued because it produces profit although not big. FRR with the calculation of net income per year / total invetasi times period, then obtained FRR yield 36.5% bigger than interest rate and get profit to invested. PPC for 43 trips which means the greater the value of PPC the longer the payback period of business investment or the smaller the value of PPC the faster the payback period of business investment Keywords : Business Analysis, Shrimp Nets, Feasibility Study, Sasak Ranah Pasisie.